The Effect of a Training Program on the Diabetic Patients Utilizing Skills of Insulin Injection Technique - Saad Hussein Murad (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: The study aims to evaluate patients’ performance toward insulin injection after training program to identify the variation in skill of patients in insulin injection technique with regard to some variable (i.e. educational level and duration of insulin injection. Methodology: A quasi experimental study has been conducted on diabetic patients. An observational checklist had been prepared which consisted of 4 main areas with 37 sub-items, which are syringe preparation for injection, insulin drawing; skin preparation for injection and insulin injection. Each of the sub-items has 2 options yes or no. One score for positive answer and zero for no. The sample of the study consisted of (n =30) males and females patients with Type 1 diabetes mellitus, who were chosen randomly from AL-Wafa’a center for diabetic treatment in Mosul-Iraq during Dec. 2003. Results: The results of the study showed that the skills performance of insulin injection was statistically different in pre from post-test (49.37%, 76.67%) respectively by using X ), the result showed significant difference at (P<0.05) level (2221.625), no significant difference between skill performance and the level of education, while significant difference appears at P 0.01 between duration of insulin injection and skill performance. The training programme has a positive effect on the skills of diabetic patients type 1 utilizing insulin injection technique.